Preparation and Properties of Anticoagulant Split Product of Fibrinogen and Its Determination in Plasma - Nanninga, L. B; Guest, M. M (Thrombosis and Haemostasis, 1967)
The anticoagulant split product resulting from fibrinolytic digestion was found by two independent methods to be 83% by weight of the initial fibrinogen. Molecular weights of the fibrinogen and the two split products were determined. A method for purification of the anticoagulant split product is described and a quantitative method to estimate this product in plasma is presented. A virtual absence of this split product was found in normal plasma, while it appeared in large amounts after fibrinolytic activation. Observations on the inhibition of clotting by the split product and blocking of the inhibition by positive dyes are presented. A similarity between the inhibition of clotting by this product and by negative dyes is suggested.